α-Synuclein Dimers Impair Vesicle Fission during Clathrin-Mediated Synaptic Vesicle Recycling - Medeiros, Audrey T.; Soll, Lindsey G.; Tessari, Isabella; Bubacco, Luigi; Morgan, Jennifer R. (Frontiers in Cellular Neuroscience, 2017)
α-Synuclein is a presynaptic protein that regulates synaptic vesicle (SV) trafficking. In Parkinson’s disease (PD) and several other neurodegenerative disorders, aberrant oligomerization and aggregation of α-synuclein lead to synaptic dysfunction and neurotoxicity. Despite evidence that α-synuclein oligomers are generated within neurons under physiological conditions, and that altering the balance of monomers and oligomers contributes to disease pathogenesis, how each molecular species of α-synuclein impacts SV trafficking is currently unknown. To address this, we have taken advantage of lamprey giant reticulospinal synapses, which are accessible to acute perturbations via axonal microinjection of recombinant proteins. We previously reported that acute introduction of monomeric α-synuclein inhibited SV recycling, including effects on the clathrin pathway. Here, we report the effects of α-synuclein dimers at synapses. Similar to monomeric α-synuclein, both α-synuclein dimers that were evaluated bound to small liposomes containing anionic lipids in vitro, but with reduced efficacy. When introduced to synapses, the α-synuclein dimers also induced SV recycling defects, which included a build up of clathrin-coated pits with constricted necks that were still attached to the plasma membrane, a phenotype indicative of a vesicle fission defect. Interestingly, both α-synuclein dimers induced longer necks on clathrin-coated pits as well as complex, branching membrane tubules, which was distinct from the clathrin coats induced by a dynamin inhibitor, Dynasore. In contrast, monomeric α-synuclein induced a buildup of free clathrin-coated vesicles, indicating an inhibition of clathrin-mediated endocytosis at a later stage during the uncoating process. Taken together, these data further support the conclusion that excess α-synuclein impairs SV recycling. The data additionally reveal that monomeric and dimeric α-synuclein produce distinct effects on clathrin-mediated endocytosis, predicting different molecular mechanisms. Understanding what these mechanisms are could help to further elucidate the normal functions of this protein, as well as the mechanisms underlying PD pathologies.